Critically Ill Patients with Renal Hyperfiltration: Optimizing Antibiotic Dose - Jorge Rico-Fontalvo; José Correa-Guerrero; María Cristina Martínez-Ávila; Rodrigo Daza-Arnedo; Tomás Rodriguez-Yanez; Amilkar Almanza-Hurtado; José Cabrales; Carmen Julia Mendoza-Paternina; Alvaro Frías-Salazar; Julio Morales-Fernández (International Journal of Nephrology)
Renal hyperfiltration (RHF) is a prevalent phenomenon in critically ill patients characterized by augmented renal clearance (ARC) and increased of elimination of renally eliminated medications. Multiple risk factors had been described and potential mechanisms may contribute to the occurrence of this condition. RHF and ARC are associated with the risk of suboptimal exposure to antibiotics increasing the risk of treatment failure and unfavorable patient outcomes. The current review discusses the available evidence related to the RHF phenomenon, including definition, epidemiology, risk factors, pathophysiology, pharmacokinetic variability, and considerations for optimizing the dosage of antibiotics in critically ill patients.